Cognitiveness and its Expression in Linguistic Categories (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, the unit of thought and the linguistic realization of the concept, which arises as a mental phenomenon, are also the result of speech and thought activity, and highlights some studies related to the interpretation of the concept in Uzbek linguistics.